Vitor Manaças : o percurso de um designer - Pereira, Cíntia Vieira Alves (2022)
The present study intends to analyze the path of the designer Vítor Manuel Teixeira Manaças (1934), considered one of the pioneers of Design in Portugal; we can say that it was one of the ones that most contributed to “the cause” of Design in Portugal. Involved in the design issue, he is a founding partner of the Portuguese Design Association, in 1976, collaborating to recognize the activity in a country where it was not yet well known. The period on which the study falls is between the end of the fifties until the beginning of the twenty-first century. and his professional trajectory is reflected in his intervention in different areas of industrial design, interior design, graphic design, museum design and, finally, his activity as a teacher. Considering the importance of his work, it is necessary to understand the path taken by Vítor Manaças, who starts in some architectural studios. In 1963 he was part of the team that designed the provisional installation of the works of the Calouste Gulbenkian Collection at the Pombal Palace, in Oeiras. Joins the Calouste Gulbenkian FCG Foundation in 1970, remains until 1994. Understanding your participation in some of the initiatives of the National Institute for Industrial Research (INII), of note is part of the team that organizes the 1st Portuguese Design Exhibition at Bolsa’s Palace, Oporto, with this path that will expand and improve your knowledge in the area of Design. As part of our approach, it is essential to understand as a teacher, what are your contributions to the teaching of design in Portugal. Our study went through two stages: the first concerning the collection of information; the second, makes a brief analysis of some of his works in the design area in order to substantiate and present to the reader the importance of the author's path.